(untitled) (Global Journal of Science Frontier Research, 2020)
An experiment was conducted to study the effect of integrated nutrient management on nutrient uptake post-harvest soil nutrient availability and nutrient balance of sweet basil (Ocimum basilicum) at ICAR -Indian Institute of Horticultural Research, Bengaluru during Kharif season of 2015 and 2016.There were nine treatments and three replication with Randomized complete block design. The results revealed that the maximum nutrient uptake in the main crop as N (155.67 and 113.19 kg ha -1 ), P (43.80 and 32.43 kg ha -1 ) and K (163.33 and 116.16 kg ha -1 ) Similarly, in ratoon (56.43 and 26.65 kg ha -1 ), (16.14 and 14.01 kg ha -1 ) and (55.65 and 39.27 kg ha -1 ) were reordered with application of both recommended FYM (10 t ha -1 ) and NPK (160:80:80 kg ha -1 ) during first and second year, respectively.